(untitled) (Malay Literature, 2014)
History has often become the inspiration for writers, as it has for Isa Kamari in the case of his novel Satu Bumi (One Earth) (1998). What were the historical sources for this author, and how were they employed in his fiction? What was the author’s aim in fictonalizing these historical sources? These are the questions that receive attention in this paper. Using a historical approach and textual analysis, the historical facts found in the novel Satu Bumi and the author’s aims behind fictionalizing them are examined in this study. The study finds that the novel Satu Bumi is based on the history of Malaysia and Singapore, and fictionalizes the historical events using elements of romance and drama. However, even in this romantic and dramatic setting, the historical elements used do not merely serve to record the history of Malaysia and Singapore but are also employed to predict the future of Malay community in Singapore, which is in an alarming state due to the island state’s physical development and a political situation that could be deemed racist, apart from the attitude of the Malay community itself. Keywords: history, historical fiction, Malays, Singapore, Malaysia